Methodology of research on older consumers - a systematic literature review - Katarzyna Bałandynowicz-Panfil (Rozprawy Społeczne)
Abstract The aging process of society changes social relations. Dynamic demographic changes lead to a significant increase in researchers' interest in particular areas of seniors' lives, including the consumption of older people. The aim of the study is to systematize current researches on older consumers.